Medium-range structure and glass forming ability in Zr–Cu–Al bulk metallic glasses. (1st May 2016) - Zhang, Pei; Maldonis, Jason J.; Besser, M.F.; Kramer, M.J.; Voyles, Paul M.
Abstract: Fluctuation electron microscopy experiments combined with hybrid reverse Monte Carlo modeling show a correlation between medium-range structure at the nanometer scale and glass forming ability in two Zr–Cu–Al bulk metallic glass (BMG) alloys. Both Zr50 Cu35 Al15 and Zr50 Cu45 Al5 exhibit two nanoscale structure types, one icosahedral and the other more crystal-like. In Zr50 Cu35 Al15, the poorer glass former, the crystal-like structure is more stable under annealing below the glass transition temperature, T g, than in Zr50 Cu45 Al5 . Variable resolution fluctuation microscopy of the MRO clusters show that in Zr50 Cu35 Al15 on sub- T g annealing, the crystal-like clusters shrink even as they grow more ordered, while icosahedral-like clusters grow. Overall, the results suggest that achieving better glass forming ability in this alloy system may depend more on destabilizing crystal-like structures than enhancing non-crystalline structures. Graphical abstract: